From guidelines to practice: A retrospective clinical cohort study investigating implementation of the early detection guidelines for cerebral palsy in a state-wide early intervention service. Issue 11 (25th November 2022) - Davidson, Sue-Anne; Ward, Roslyn; Elliott, Catherine; Harris, Courtenay; Bear, Natasha; Thornton, Ashleigh; Salt, Alison; Valentine, Jane
Abstract : Objectives: To report on knowledge translation strategies and outcomes from the implementation of the early detection guidelines for cerebral palsy (CP) in a state-wide tertiary early intervention (EI) service and investigate the impact of social determinants on clinical services. Design: Retrospective longitudinal cohort study. Setting: The Western Australia tertiary paediatric EI service. Participants: EI clinicians, consumers and children using the EI service. Outcome measures: Knowledge translation strategies including consumer perspectives, clinician training and Communities of Practice (CoP) guided implementation. We measured changes in referral number and age, delivery of early detection and intervention following the implementation of the guidelines. Exposure to adverse childhood experiences (ACEs), appointment non-attendance (DNA) rates, remoteness and socioeconomic quintiles were used to measure social determinants of health using negative binomial (Incidence Rate Ratios, IRR) and logistic regression (Odds Ratios, ORs). Results: Ten consumers participated in Focus Groups, 100 clinicians were trained and 22 clinicians established a monthly CoP. Referrals increased fourfold to 511 children. Corrected gestational age at referral decreased from a median of 16.1 to 5.1 months (p<0.001) and at first appointment from 18.8 to 6.8 months (p<0.001). Children living in social disadvantage had the highest DNA risk (quintile 1 vs 5: IRR 2.2, 95% CI 1.1 to 4.6, p=0.037). Children exposed to ACEs had higher odds of living in social disadvantage (quintile 1 vs 5, OR=3.8, 95% CI 1.4 to 10.0, p=0.007). No significant association was found between remoteness and DNA rate or ACE score. Conclusions: Implementation strategies reduced referral age and improved the delivery of early detection assessments. Further investigation of the association between social disadvantage, DNA risk and ACE score is required in the development of a state-wide early detection network.